Teori dalam Penelitian Media - Kartini Kartini; Imam Azhari Harahap; Nazmia Yusdi Arwana; Suci Wahyu Tami Br Rambe (Universitas Muhammadiyah Enrekang, 2022)
Social media can also be said to be network media that can strengthen social relationships between users. Social media is a medium on the internet where users can present, interact, collaborate, share, connect with others and create virtual social girlfriend connections. Social media is digital media where social reality occurs and users interact in space. Media exposure is more complicated than access. Because it depends not only on who the person is physically (certain level of media access), but also on whether the person is actually exposed to the message. Exposure is listening to, watching, reading, and generally experiencing multimedia news with little interest. Exposures can be individual or group.